Adverse effects of engineered nanomaterials : exposure, toxicology, and impact on human health - Fadeel, Bengt; Pietroiusti, Antonio; Shvedova, Anna A. (Elsevier/Academic Press, 2017)
Bio-nano interactions / Dana Westmeier, Shirley K. Knauer, Roland H. Stauber, Dominic Docter -- Physicochemical characterization / Kristen Rasmussen, Hubert Rauscher, Agnieszka Mech -- Toxicity tests / Maria Dusinska, Elise Rundén-Pran, Jurgen Schnekenburger, Jun Kanno -- Computational approaches / Tu C. Le, Vidana Epa, Lang Tran, Dave Winkler -- Exposure Assessment / Kai Savolainen, Antonio Pietroiusti -- Biomonitoring / Enrico Bergamaschi, Irirna Guseva Canu, Adriele Prina-Mello, Regulation and legislation / Kirsten Rasmussen, Brigit Sokull-Klüttgen, IL Je Yu, Jun Kanno, Akihiro Hirose, Maureen R. Gwinn -- Risk assessment and risk management / Robert Landsiedel, Ursula G. Sauer, Wim H De Jong -- Respiratory system, part one / Craig A. Plooand, Ken Donaldson -- Respiratory system, part two / Harri Alenius, Michael R. Shurin, Galina V. Shurin, Don Beezhold, Anna A. Shvedova -- Cardiovascular system / Jennifer B. Raftis, Nicholas L. Mills, Rodger Duffin -- Neurological system / Myrtill Simkó, Mats-olof Mattsson, Robert A. Yokel -- Immune system / Diana Boraschi, Bengt Fadeel, Albert Duschl -- Endorine system / Xuefei Lu, Yong Zhu, Tao Zhu -- Skin / Nancy A. Monteiro-Riviere, Francesca Larese Filon -- Gastrointestinal system / Mark A. Jepson, Hans Bouwmeester -- Reproduction and development / Luisa Campagnolo, Karin S. Hougard -- Genotoxicitiy and cancer / Shareen H. Doak, Ying Liu, Chunying Chen
Keywords: Environmental Exposure -- adverse effects; Nanostructured materials -- Health aspects; Nanostructures -- adverse effects; Nanostructures -- toxicity; Risk Assessment; Toxicology